2010
DOI: 10.1063/1.3524523
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of nanoscale density fluctuations using electron microscopy: Light-localization properties of biological cells

Abstract: We report a study of the nanoscale mass-density fluctuations of heterogeneous optical dielectric media, including nanomaterials and biological cells, by quantifying their nanoscale light-localization properties. Transmission electron microscope images of the media are used to construct corresponding effective disordered optical lattices. Light-localization properties are studied by the statistical analysis of the inverse participation ratio ͑IPR͒ of the localized eigenfunctions of these optical lattices at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(70 citation statements)
references
References 15 publications
3
67
0
Order By: Relevance
“…For this, mass arrays and then dielectric arrays were created from the confocal imaging of the cells, then the normal modes of light waves were obtained. This was followed by the quantification of the amount of the morphological distortion, L md , by taking the average of the square of the intensity of the normal modes, using a very similar methodology described elsewhere 1719 .…”
Section: Resultsmentioning
confidence: 99%
“…For this, mass arrays and then dielectric arrays were created from the confocal imaging of the cells, then the normal modes of light waves were obtained. This was followed by the quantification of the amount of the morphological distortion, L md , by taking the average of the square of the intensity of the normal modes, using a very similar methodology described elsewhere 1719 .…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that << IPR ( L )> Pixel > value is proportional to the product of the amplitude of the refractive index fluctuation and its correlation. Overall, the validation study in (24) showed that nanoscale disorder can be quantified by the IPR technique, which can distinguish statistically significant differences between the two disordered systems of minute difference in disorder.…”
Section: Previous Studies Using the Ipr Analysismentioning
confidence: 94%
“…A short description was presented in (24) about the methodology, but here we present the methodology in detail (Section 2). Then we reviewed in brief our previous results (24) to provide a background for the present study (Section 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, mass arrays and then dielectric arrays were created from the confocal imaging of the cells, then the normal modes of light waves were obtained. This was followed by the quantification of the amount of the morphological distortion, L md , by taking the average of the square of the intensity of the normal modes, using a very similar methodology described elsewhere [17][18][19] .…”
Section: Muc13 and Her2 Co-localization Is Associated With Nanoscale mentioning
confidence: 99%